Key proteins of proteome underlying sperm malformation of rats exposed to low fenvalerate doses are highly related to P53. Issue 6 (3rd March 2021) - Huang, Shaoping; Lu, Ying; Li, Suying; Zhou, Tao; Wang, Jing; Xia, Jiangyan; Zhang, Xinxin; Zhou, Zuomin
Abstract: Fenvalerate (Fen) is an endocrine disruptor, capable of interfering with the activity of estrogen and androgen. Our objective was to explore the molecular mechanisms of Fen on sperm in vivo. Adult male Sprague–Dawley rats were orally exposed to 0, 0.00625, 0.125, 2.5, 30 mg/kg/day Fen for 8 weeks. Sperm morphology, differential proteomics of sperm and testes, bioinformatic analysis, western blotting (WB), and RT‐PCR were used to explore the mechanism of Fen on sperm. Data showed that low Fen doses significantly induced sperm malformations. In sperm proteomics, 47 differentially expressed (DE) proteins were enriched in biological processes (BPs) related to energy metabolism, response to estrogen, spermatogenesis; and enriched in cellular components (CCs) relating to energy‐metabolism, sperm fibrous sheath and their outer dense fibers. In testicular proteomics, 56 DE proteins were highly associated with mRNA splicing, energy metabolism; and enriched in CCs relating to vesicles, myelin sheath, microtubules, mitochondria. WB showed that the expression of selected proteins was identical to their tendency in 2D gels. Literature indicates that key DE proteins in proteomic profiles (such as Trap1, Hnrnpa2b1, Hnrnpk, Hspa8, and Gapdh) are involved in P53‐related processes or morphogenesis or spermatogenesis. Also, P53 mRNA and protein levels were significantly increased by Fen; bioinformatic re‐analysis showed that 88.5% DE proteins and P53 formed a complex interacting network, and the key DE proteins were coenriched with P53‐related BPs. Results indicate that key DE proteins of proteome underlying sperm malformations of rats exposed to low Fen doses are highly related to P53.